Cooperation search algorithm for tuning automatic voltage regulator system - Widi Aribowo; Bambang Suprianto; Unit Three Kartini (Institute of Advanced Engineering and Science, 2022)
The cooperation search algorithm (CSA) duplicates teamwork in every part of the company. This paper presents an approach to setting automatic voltage regulator (AVR) with proportional-integral-derivative (PID) control based on CSA. To get the performance of the proposed method, this paper uses the maximum overshoot, rise time, settling time, and error. This paper uses the whale optimization algorithm (WOA), grasshopper optimization algorithm (GOA), particle swarm optimization (PSO), and sine-cosine algorithm (SCA) methods as a comparison in measuring the performance of the CSA method which is used as the optimization of PID parameters on the AVR. From the simulation, the application of the CSA method to get the optimal PID parameter value has an average result that can reduce the maximum overshoot by 10.97% compared to the GOA, PSO and SCA methods.